<htm>Flora Fanerogâmica do Estado do Paraná, Brasil: Psilochilus Barb.Rodr. (Orchidaceae, Triphorinae)</htm> - Ceschin, Fernanda; Mancinelli, Werner S.; SMIDT, ERIC DE C. (Acta Biológica Paranaense, 2012)
<htm>Flora Fanerogâmica do Estado do Paraná, Brasil: Psilochilus Barb.Rodr. (Orchidaceae, Triphorinae)</htm>